2013
DOI: 10.1016/j.earscirev.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Concepts of hydrological connectivity: Research approaches, pathways and future agendas

Abstract: . (2013) 'Concepts of hydrological connectivity : research approaches, pathways and future agendas.', Earth-science reviews., 119 . pp. 17-34. Further information on publisher's website:http://dx.doi.org/10.1016/j.earscirev.2013.02.001Publisher's copyright statement: NOTICÅ: this is the author's version of a work that was accepted for publication in Earth-Science Reviews. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
449
0
11

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(464 citation statements)
references
References 118 publications
4
449
0
11
Order By: Relevance
“…The developments in hydrological connectivity were driven partly by calls for new ways of thinking about runoff and hydrological process conceptualization in heterogeneous landscapes (McDonnell, 2003;Ambroise, 2004;McDonnell et al, 2007). Hydrological connexions via overland and subsurface flows have become conceptualized as a function of water volume (supplied by rainfall and runon, depleted by infiltration, evaporation, transpiration and transmission losses) and rate of transfer (a function of pathway, hillslope length and flow resistance) (Bracken et al, 2013). These processes interact with flow resistance, varying as a function of flow depth, which establishes a feedback between rainfall, infiltration and flow routing which produces the nonlinearity seen in river hydrographs and scale-dependence of runoff coefficients (Wainwright and Bracken, 2011).…”
Section: Existing Conceptual Framework Of Sediment Connectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The developments in hydrological connectivity were driven partly by calls for new ways of thinking about runoff and hydrological process conceptualization in heterogeneous landscapes (McDonnell, 2003;Ambroise, 2004;McDonnell et al, 2007). Hydrological connexions via overland and subsurface flows have become conceptualized as a function of water volume (supplied by rainfall and runon, depleted by infiltration, evaporation, transpiration and transmission losses) and rate of transfer (a function of pathway, hillslope length and flow resistance) (Bracken et al, 2013). These processes interact with flow resistance, varying as a function of flow depth, which establishes a feedback between rainfall, infiltration and flow routing which produces the nonlinearity seen in river hydrographs and scale-dependence of runoff coefficients (Wainwright and Bracken, 2011).…”
Section: Existing Conceptual Framework Of Sediment Connectivitymentioning
confidence: 99%
“…Each zone contains two parts: the morphologic system (the landforms) and the cascading system (the energy and materials flowing through that zone) (Chorley, 1971;Schumm, 1981). A major limitation of previous discussions of 'connectivity' is an unclear definition of the meaning of the term within the context in which it is used (Bracken et al, 2013). In a geomorphic system, connectivity may occur through the physical contact between two zones, through the transfer of material between zones, or both (Jain and Tandon, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The designs of ditch networks, including reach morphology, reach branching, and density, are also strongly related to the runoff capture efficiency (Levavasseur et al 2012;Zhang et al 2013). Moreover, it is expected that the influence of plotstream connections on runoff interception (Bracken et al 2013) is similar to that of plot-ditch connections, although this has not been demonstrated.…”
Section: Waterlogging Controlmentioning
confidence: 99%
“…Hydrological connectivity is the basis of water supply and allocation; it should be the first to be analyzed in quantitative studies of how waterways in neighboring regions can be connected in water management. Bracken et al (2013) classified the research around hydrological connectivity into five broad themes based on: i) soil moisture; ii) flow processes; iii) terrain; iv) models; and v) indices. This classification yielded a definition of hydrological connectivity, and laid a foundation of conceptualization and methodology of different research approaches.…”
Section: Introductionmentioning
confidence: 99%